Efeito da administração de somatotropina pré-parto em novilhas da raça Holandês com elevada condição corporal sobre parâmetros metabólicos, reprodutivos e produção leiteira - Acosta, Diego Andres Velasco (2012)
Negative energy balance (NEB) has been associated with changes in hormones that support follicular development in early lactation. Prepartum recombinant bovine somatotropin (rbST) injection led to reduced non-esterified fatty acids (NEFA) and β-hydroxybutyrate (BHBA) in the early postpartum period. Therefore, prepartum administration of somatotropin may result in metabolic changes that benefit the energetic balance of the postpartum dairy cows. The aim of this study was to determine the effect of prepartum injections of somatotropin in dairy heifers with high BCS on the markers of NEB, resumption of ovarian activity and milk production. Holstein heifers (n=20) with high body condition score (scale 1-5; BCS>3.5) were randomly divided into two groups: somatotropin group (n=10) that received two doses of 500 mg of rbST at -28 and -14 days from calving; and control group (n=10) that received applications of placebo in a similar manner to somatotropin group. Blood samples were collected weekly from 28 to 42 d after calving to evaluate BHBA and NEFA concentrations. Follicular development was also monitored via ultrasound examinations starting at days 10 postpartum and every 3 days until ovulation. Prepartum somatotropin administration did not affect (P =0.28) the moment of the first postpartum ovulation. The proportion of cows ovulating the first follicular wave postpartum was not different between groups (P=0.49). There was no effect (P>0.05) of prepartum treatment on the diameter of the first postpartum dominant follicle. There was a interaction days by group for plasma NEFA concentrations during the prepartum period (P= 0.03) and a tendency for the day (P=0.07) but no effect on the group (P=0.35). There was only an effect of the week (P<0.001) for postpartum NEFA concentrations. Postpartum NEFA concentration was higher at days 0, 7 and 14 than at 21, 28, 35 and 42 (P<0.05). For pre and postpartum BHBA there was not effect of days (P>0.05), group (P>0.05) or days by group (P=0.05). In conclusion, prepartum somatotropin treatment in dairy heifers with high body condition did not improve parameters that indicate that these heifers had a less severe NEB during the early postpartum period,had not affect development of the first follicular wave in the postpartum period and milk production.